The genre transformation of the historical novel in the adventure-philosophical science fiction of the 20th century - Козьмина, Елена (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2012)
This article addresses the problem of adventure-historical novel genre transformation in the adventure-philosophical science fiction of the 20th century and the variation of genre meaning related to this transformation. For this purpose, we analyse the Strugatskys’ novel, Hard to be a God.